PEMANFAATAN SMARTPHONE DALAM MENERAPKAN MARKETING 4.0 BERDASARKAN TEORI DIFUSI INOVASI (Studi Kasus Usaha Mikro Kecil Menengah Rumah Bordir Minang) - Sahara Sahara (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
This study aims to get an overview of the use of smartphones in implementing marketing 4.0 based on the theory diffusion of innovation. The results of this study conclude that by adopting marketing 4.0, UMKM Rumah Bordir Minang apply some new innovations products with new innovations by adding types of embroidery products, marketing them online and offline such as joining buying and selling forums in market places, another innovations by doing live Facebook, live Instagram and Tik Tok as well as offline such as making pamphlets, so due to the pandemic so exhibitions and bazaars cannot be carried out. This research used qualitative method, combining the methods of structured interviews, in-depth interviews and observations of the Rumah Bordir Minang in Bukittinggi City. With the existence of a smartphone, Rumah Bordir Minang has felt enormous benefits compared to the conventional way, because it can reduce the amount of costs and time spent in the process of selling embroidery products as well as expanding market share and increasing sales turnover.